2014
DOI: 10.1536/ihj.13-201
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Late-Onset Residual Aortopulmonary Septal Defect Using a Muscular Ventricular Septal Occluder

Abstract: SummaryLate-onset residual shunt after surgical repair of aortopulmonary septal defect (APSD) is a rare event complicating the management strategy. Surgical reoperation was the treatment of choice traditionally, while associated with increased risk and suffering. We report a case of successful treatment of this type of residual shunt using a transcatheter closure technique with an infrequently used muscular ventricular septal device. (Int Heart J 2014; 55: 89-91)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In recent years, transcatheter closure has been included as a treatment option, but it has not yet become the standard treatment, with studies conducted on this treatment being generally case reports. In conclusion, this field has limited experience . No devices have been specifically developed yet for the closure of APW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, transcatheter closure has been included as a treatment option, but it has not yet become the standard treatment, with studies conducted on this treatment being generally case reports. In conclusion, this field has limited experience . No devices have been specifically developed yet for the closure of APW.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional treatment method is surgery. Although the results of surgical treatment are satisfactory, complications such as cardiopulmonary bypass‐related problems, residual defects, infective endocarditis, pulmonary artery stenosis development, or coronary artery injury may develop . In a study of 43 patients who received surgical treatment, six (14% mortality rate) of the patients died, and the presence of accompanying cardiac abnormalities and weight <2.5 kg during the operation were associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It is categorized into three types by Mori: (1) type I or proximal defect, which is located 1-1.5 cm away from the aortic valve, (2) type II or distal defect, which appears and disappears between the distal ascending aorta and the pulmonary artery, and (3) type III or the complete defect [8] . At present, the right pulmonary artery that originates from the aorta is classified as type IV defect [9,10] . In this case study, the patient suffers from an extremely rare deformity, i.e ., type I combined with type IV.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the value of cardiac 64-slice computed tomography in APW diagnosis of this case was remarkable. In our case, the key to the correct diagnosis of the APW was to find the simultaneous development of the aorta and pulmonary trunk through an ascending aortogram in the right anterior oblique position [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Naik et al [1 ]and Peer et al [4 ]used an Amplatzer ASD device to close a 6.0-mm APW and an Amplatzer duct occluder to close a 3.0-mm APW. In addition to these studies, Li et al [8] reported the successful treatment of a residual shunt after surgical repair of an APW with a muscular ventricular septal occluder. In our experience, one critical requirement in choosing an appropriate closure device is that the candidate device should match the shape and margin of the defect.…”
Section: Discussionmentioning
confidence: 99%